THE MOST SIGNIFICANT MORPHOLOGICAL FEATURES OF THIRD MOLARS IN ADULT PERSONS ACCORDING TO ORTHOPANTOMOGRAPHY - Talash, R.V. (World of Medicine and Biology, 2020)
The article presents a theoretical generalization and a new solution of the scientific problem, which consists in determining the morphological features of third molars according to orthopantomography. A literature review, the analysis results of the dentition orthopantomograms of persons in the first period of mature age, randomly selected in the clinic, are presented. A systematic analysis of the general visual representation of third molars’ morphological features in people of mature age, was carried out based on orthopantomograms selection. Morphological features of third molars, forms of retention, types of dystopia, morphological differences between impacted and embedded third molars were established. The systematic approach used in the work permitted to put in order the variational polymorphism of anomalously developed third molars’ forms, while identifying the most indicative signs for their classification.
Keywords: teeth; third molars; orthopantomogram; retention; dystopia